Critical shear rate and torque stability condition for a particle resting on a surface in a fluid flow. (2nd November 2016) - Kudrolli, Arshad; Scheff, David; Allen, Benjamin
Abstract : We advance a quantitative description of the critical shear rate [STIX]x1D6FE_c needed to dislodge a spherical particle resting on a surface with a model asperity in laminar and turbulent fluid flows. We have built a cone-plane experimental apparatus which enables measurement of [STIX]x1D6FE_c over a wide range of particle Reynolds number Re_p from 10^-3 to 1.5× 10^3 . The condition to dislodge the particle is found to be consistent with the torque balance condition after including the torque component due to drag about the particle centre. The data for Re_p<0.5 are in good agreement with analytical calculations of the drag and lift coefficients in the Re_p→ 0 limit. For higher Re_p, where analytical results are unavailable, the hydrodynamic coefficients are found to approach a constant for Re_p>1000 . We show that a linear combination of the hydrodynamic coefficients found in the viscous and inertial limits can describe the observed [STIX]x1D6FE_c as a function of the particle and fluid properties.